Kombinasi adsorben biji kelor - zeolit alam Lampung untuk meningkatkan efektivitas penjerapan logam Pb dalam air secara kontinu pada kolom fixed bed adsorber - Simparmin Br. Ginting; Sebastian Djoni Syukur; Yeni Yulia (Jurnal Rekayasa Proses, 2017)
The mixture of adsorbents of moringa seed (BK) and natural zeolite of Lampung (ZAL) is placed in a fixed bed adsorber column arranged at a certain height according to the designed height ratio. BK is processed by extraction to remove its oil content while ZAL is activated by chemical and physical treatments. Composition ratio of BK-ZAL (cm/cm) was varied i.e.1:1, 1:2 and 1:3 and concentrations of Pb entering adsorber were 1 ppm and 2 ppm. The adsorption conditions were 20-35 mesh adsorbent size, 4 cm diameter column of adsorber, 5 cm bed height, and 8 liters/3 hours flowrate. Upflow adsorption was performed in a fixed bed adsorption column for 3 hours and Pb solution of output adsorber was taken at every 30 minutes. Analysis of Pb content was performed by Atomic Absorption Spectroscopy (AAS). Adsorbent BK before and after extracted, and after adsorption were characterized using Fourier Transmission Infra Red (FTIR). ZAL before and after activation were characterized using X-Ray Diffraction (XRD), X-Ray Fluorescence (XRF), and Fourier Transmission Infra Red (FTIR). The characterization results of XRD, XRF and FTIR showed that the crystalline phases of ZAL increased, the activation process of ZAL only caused a shift in the peak, no significant change in the structure of solids, and the content of impurities in ZAL reduced after activation, thereby enhancing its ability to adsorb Pb. AAS analysis results showed that the best combination adsorbent BK-ZAL (cm/cm) was 1: 2 with the highest effectiveness of the entrapment of Pb metal reached 99.90%. The adsorption capacity of adsorbent was 2.25 mg Pb/ gram adsorbent calculated using Freundlich equilibrium model.